Tenth Five Year Plan (2002-07) Draft Annual Plan 2006-07 Special Component Plan - Planning Commission (Planning Commission, 2006)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal; Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast, about 162 kms. south of Chennai is the largest of these and consists of 12 scattered areas interspersed with enclaves of Villupuram district and Cuddalore District of Tamilnadu. Karaikal region is about 150 Kms. south of Pondicherry and it is surrounded by Nagapattinam District of Tamilnadu. Yanam region is located about 840 kms. north east of Pondicherry near Kakinada in Andhra Pradesh. Mahe region lies almost parallel to Pondicherry 653 kms. away on the west coast near Tellicherry in Kerala Area and Population The Union Territory of Pondicherry is 480 sq.kms. in area and has a population of 9,74,345 consisting of 4,86,961 males and 4,87,384 females according to 2001 census. The region-wise breakup is as follows
Government of Pondicherry Planning and Research Department